Astragalus and Ginseng Polysaccharides Improve Developmental, Intestinal Morphological, and Immune Functional Characters of Weaned Piglets - Yang, C. M.; Han, Q. J.; Wang, K. L.; Xu, Y. L.; Lan, J. H.; Cao, G. T. (Frontiers in Physiology, 2019)
Antibiotic resistance is a major issue in animal industries and antibiotic-free alternatives are needed to treat infectious diseases and improve performance of pigs. Plant extracts have been suggested as a potential solution. The present study was conducted to investigate the effects of Astragalus polysaccharides (Aps) and ginseng polysaccharide (Gps) on growth performance, intestinal morphology, immune function, volatile fatty acids (VFAs), and microfloral community in weaned piglets. A total of 180 weaned piglets were randomly divided into three treatment groups during a 28-d feeding experiment, including a basal diet (Con), basal diet supplemented with the 800 mg/kg Aps (Aps), and basal diet supplemented with 800 mg/kg Gps (Gps). The results showed that Aps and Gps increased body weight and the average daily gain and feed conversion rate, and reduced the rate of diarrhea. Gps also decreased aspartate aminotransferase compared to the Con piglets after 14 d. No significant effects on alanine aminotransferase were observed. Both Aps and Gps piglets exhibited higher immunoglobulin M levels after 14 and 28 d, and also decreased jejunal crypt depth, increased jejunal villus length and villus height/crypt depth ratio, and increased expression of tests toll-like receptor 4, myeloid differentiation primary response 88, nuclear factor-kappa B proteins in the jejunum. Aps and Gps piglets also had higher concentrations of acetic acid, isobutyric acid, and butyrate in their colon. Result of high-throughput sequencing revealed that Aps and Gps affected bacterial quantity and diversity in the colon. Species richness and evenness were higher in both Aps and Gps piglets than the control piglets. Aps and Gps piglets also had a higher relative abundance of Lachnospiraceae and Anaerostipes, and the Aps piglets had a higher relative abundance of Lactobacillus gasseri and Lactobacillus amylovorus. Therefore, dietary supplementation with Aps and Gps could be beneficial for optimizing the performance of industry pigs and reducing dependence on antibiotics. Furthermore, Plant polysaccharides play a great role in promoting the sustainable development of animal husbandry.